Endometriosis-associated cancer: modern aspects of etiopathogenesis, treatment and rehabilitation - E. Begovich; A. G. Solopova; V. O. Bitsadze; S. V. Khlopkova; E. A. Orudzhova (IRBIS LLC, 2021)
Aim: to analyze current literature sources on endometriosis-associated cancer (ЕАС) in gynecology.Materials and Methods. We searched for publications in the international scientific databases: eLibrary, Google Scholar, ScienceDirect, Cochrane Library, PubMed/MEDLINE and clinical research registries. For this systematic analysis, only full-text publications were used. We evaluated the reliability of evidence and the methodological quality of the studies. The data on the modern approach to the therapy and rehabilitation of women with external genital endometriosis (EGE) are presented. Search terms for publications in Russian and English were used: «endometriosis», «endometriosis-associated ovarian neoplasia», «oncology», «rehabilitation».Results. Despite the fact that EGE is considered a benign disease, there is a risk for its malignant transformation. However, the pathogenesis and pathomorphological mechanisms of ЕАС are not yet fully understood.Conclusion. Active management of the rehabilitation period for women with EGE provides an opportunity for early diagnosing recurrences that will provide early diagnostics ovarian ЕАС and improve the main indicators of the quality of life for such patients.